2016
DOI: 10.1016/j.jpain.2016.01.043
|View full text |Cite
|
Sign up to set email alerts
|

(140) Prevalence of chronic pain and comorbid medical conditions associated with diabetes in Kuwait: a random sample telephone survey

Abstract: essential for providers to identify patients at risk for prolonged opioid use. As a first step, our research identifies significant patient characteristics that may predict prolonged opioid use and associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systematic review of 48 studies showed 30% frequency of CP worldwide [13]. However, regional reports of CP prevalence reported from different parts of the world are as follows: 19% in Libya [43], 24% in Iran [44], 56% in Kuwait [45] as a function of participants’ age. Around 40.5% adolescents reported CP in Latvian adults [46].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 48 studies showed 30% frequency of CP worldwide [13]. However, regional reports of CP prevalence reported from different parts of the world are as follows: 19% in Libya [43], 24% in Iran [44], 56% in Kuwait [45] as a function of participants’ age. Around 40.5% adolescents reported CP in Latvian adults [46].…”
Section: Discussionmentioning
confidence: 99%